2009
DOI: 10.1002/chem.200802656
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Pyrimidines and Triazines in Ice: Implications for the Prebiotic Chemistry of Nucleobases

Abstract: Herein, we report the efficient synthesis of RNA bases and functionalized s-triazines from 0.1 M urea solutions in water after subjection to freeze-thaw cycles for three weeks. The icy solution was under a reductive, methane-based atmosphere, which was subjected to spark discharges as an energy source for the first 72 h of the experiment. Analysis of the products indicates the synthesis of the s-triazines cyanuric acid, ammeline, ammelide, and melamine, the pyrimidines cytosine, uracil, and 2,4-diaminopyrimidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
93
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(98 citation statements)
references
References 29 publications
2
93
0
1
Order By: Relevance
“…This ordering through assembly could then provide a catalyst for polymerization of protonucleic acid polymers, by aligning their functional groups. Additionally, these molecules are attractive protonucleic acid nucleobase candidates, as triaminopyrimidine forms glycosidic linkages with ribose to produce nucleosides in water, and barbituric acid, cyanuric acid, and melamine have been found in model prebiotic reactions [142,143].…”
Section: Selectionmentioning
confidence: 99%
“…This ordering through assembly could then provide a catalyst for polymerization of protonucleic acid polymers, by aligning their functional groups. Additionally, these molecules are attractive protonucleic acid nucleobase candidates, as triaminopyrimidine forms glycosidic linkages with ribose to produce nucleosides in water, and barbituric acid, cyanuric acid, and melamine have been found in model prebiotic reactions [142,143].…”
Section: Selectionmentioning
confidence: 99%
“…At high concentrations, urea is considered an important prebiotic reactant in the synthesis of pyrimidines [22] [23]. Its role as a prebiotic reagent remains doubtful due to its instability at the high concentrations needed to act as a prebiotic intermediate [24].…”
mentioning
confidence: 99%
“…Subsequent Miller-like experiments, run with other types and combinations of gases (24, 25) representing plausible geochemical conditions, produced other classes of basic building block molecules, namely sugars and nucleotides. To date, all of the major classes of organic compounds found in biological systems have been synthesized in experiments of this nature; in particular, in the most recent study of Miller and coworkers (26), it was shown that a CO-CO 2 -N 2 -H 2 O atmosphere can give a variety of bioorganic compounds with yields comparable to those obtained from a strongly reducing atmosphere, suggesting that atmospheres containing carbon monoxide might therefore have been conducive to prebiotic synthesis and perhaps the origin of life.Theory and modeling have generally provided considerable insight (27) in prebiotic chemistry, particularly by studying the synthesis of simple organic molecules and the mechanisms and barriers of such reactions on substrates such as ice (28,29) or minerals (30,31). A remarkable theoretical study, based on ab initio molecular dynamics (AIMD), on prebiotic synthesis focused on the simulation of the effect of the pressure/temperature shock waves induced by the impact of bolides in the early Earth (17).…”
mentioning
confidence: 99%